THE ROLE OF GENERATION Z IN VILLAGE DEVELOPMENT THROUGH DIGITAL TECHNOLOGY INNOVATION - Sarjito, Aris (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
Rural areas face significant challenges in adopting digital technology due to limited internet infrastructure, low digital literacy, financial constraints, and sociocultural resistance. However, Generation Z has emerged as a key driver of rural digital transformation, utilizing e-commerce, AgriTech, digital marketing, and e-learning to boost economic and social development. This study aims to analyze the role of Generation Z in rural digital innovation, explore key challenges, and propose strategic solutions. A qualitative research approach with case study analysis was employed, examining youth-led digital initiatives in various rural regions. The findings indicate that digital technology has increased market accessibility, improved agricultural productivity, and enhanced educational opportunities for rural communities. However, achieving sustainable digital transformation requires strengthening digital infrastructure, implementing youth capacity-building programs, fostering government-private collaborations, and encouraging community engagement. The study recommends policy interventions to expand broadband access, financial support for youth entrepreneurs, and intergenerational digital literacy programs. Future research should focus on the long-term economic impact of digital transformation and the integration of artificial intelligence and blockchain in rural development. Keywords: digital transformation, e-commerce, generation z, rural development, smart agriculture